Evaluation of the antioxidant and hepatoprotective activity of Mucuna pruriens (L) cv. utilis forage meal and their polyphenols extract in Sprague Dowley rats - Scull, Idania; Savón, Lourdes; Spengler, Iraida; Herrera, Magaly (Cuban Journal of Agricultural Science, 2020)
In order to evaluate the antioxidant and hepatoprotective effect of Mucuna pruriens (L) cv. utilis forage meal and their polyphenol extract, an intoxication model induced with carbon tetrachloride (CCl4) was used. A total of 60 Sprague Dowley rats from both sex of 7-8 weeks of age were used, distributed in three treatments, according to a completely random design. The treatments consisted in a control group with EAO-1004 diet, which contained the premixture with antioxidants, and two experimental groups, which was supplied the Mucuna pruriens forage meal and their polyphenol extract, in a dose of 300 mg/kg body weight respectively, in replacement of the control diet premixture. All groups received the diet of their treatments and water ad libitum. At the end of the experimental period (30d), the animals were slaughtered and biochemical blood indicators were studied, the alanine aminotransferase (ALT) and the aspartate aminotransferase (AST) enzymes were quantified. The activity of the catalase antioxidant enzyme and the antioxidant state of the animals were also determined. The increase of the catalase enzyme concentration in liver (10.42 UI/L) and blood serum (20.50 UI/L) showed that the meal and their extract change the redox state caused by the CCl4.The forage meal and their polyphenols extract showed its hepatoprotective effect against the damage action of the CCl4,evaluated by the alanine aminotransferase and aspartate aminotransferase. The results showed that it is possible to use, in diets for rats the forage meal and their polyphenols extract with antioxidants effects similar to those of the control diet, which used synthetic antioxidants, vitamins and minerals. It is suggested to developed similar studies in productive animals, that includes studies of doses optimization for different animal categories. Key words: oxidative stress, serum polyphenols, catalase, aspartate aminotransferase.